New records of sea cucumbers Phyllophorus (Phyllothuria) cebuensis (Semper) and Trachasina crucifera (Semper) from the south-west coast of India - Deepa, R P; Biju Kumar, A (Indian Journal of Fisheries, 2012)
The paper describes two species of sea cucumbers, Phyllophorus (Phyllothuria) cebuensis (Semper) (Family Phyllophoridae) recorded for the first time from the south-west coast of India and Trachasina crucifera (Semper) (Family Cucumariidae) reported for the first time from the Indian coasts